1994
DOI: 10.1063/1.468499
|View full text |Cite
|
Sign up to set email alerts
|

Critical behavior of ionic micellar systems at different salt concentrations

Abstract: The coexistence curves of the system dodecylammonium chloride+water+KCl have been measured at different salt concentrations. The results can be described with the usual Ising 3-D value for the critical exponent β=0.325. The analysis of the diameter indicates that the correct order parameter is defined in terms of an effective concentration calculated according to Eq. (4). Both the order parameter and the diameter of the coexistence curve point out that the range of validity of simple scaling decreases with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
35
2

Year Published

1998
1998
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 36 publications
3
35
2
Order By: Relevance
“…Although the error in determination of b is as large as among the three. This is in contradiction with that reported by Martin et al (1) and is in agreement with our previous {0.01, all the values of b for the three variables in the temperature range of 1 K approach to 3D Ising value within work (9).…”
Section: Introductionsupporting
confidence: 44%
See 2 more Smart Citations
“…Although the error in determination of b is as large as among the three. This is in contradiction with that reported by Martin et al (1) and is in agreement with our previous {0.01, all the values of b for the three variables in the temperature range of 1 K approach to 3D Ising value within work (9).…”
Section: Introductionsupporting
confidence: 44%
“…The experimental results are analyzed to determine the critical exponent b and Critical microemulsion and micellar systems are of conto examine the size of asymptotical range and the anomalies siderable interest because a controversy from experiments of the diameters for different choices of order parameters. and theories was raised about whether these systems near the critical points belonged to the 3D Ising universality class MATERIALS AND METHODS (1,2). Most of the experiments (2, 3) involved measurements of critical exponents n, g, and a, which characterize Materials the divergence of the correlation length and osmotic compressibility and the specific heat at constant pressure and…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) Critical microemulsions and micellar systems are of considerable interest because of the question of whether these systems near the critical point belong to the universality class of three-dimensional Ising-like system. (9,10) Most of the experiments involved measurements of critical exponents ν, γ , and α which characterize the divergence of correlation length, the osmotic compressibility, and the specific heat at constant pressure and the critical concentration. (4)(5)(6)(11)(12)(13) Some of experimental results showed that the micellar systems behaved as three-dimensional Ising systems.…”
Section: Introductionmentioning
confidence: 99%
“…(4)(5)(6)(11)(12)(13) Some of experimental results showed that the micellar systems behaved as three-dimensional Ising systems. A few experimental studies (9,12) have been carried out to determine the critical exponent β, which characterizes the shape of the coexistence curve. The results were not precise enough to unambiguously support the Ising or Fisher renomalization value.…”
Section: Introductionmentioning
confidence: 99%